What makes the dorsomedial frontal cortex active during reading the mental states of others? - Isoda, Masaki; Noritake, Atsushi (Frontiers in Neuroscience, 2013)
The dorsomedial frontal part of the cerebral cortex is consistently activated when people read the mental states of others, such as their beliefs, desires, and intentions, the ability known as having a theory of mind (ToM) or mentalizing. This ubiquitous finding has led many researchers to conclude that the dorsomedial frontal cortex (DMFC) constitutes a core component in mentalizing networks. Despite this, it remains unclear why the DMFC becomes active during ToM tasks. We argue that key psychological and behavioral aspects in mentalizing are closely associated with DMFC functions. These include executive inhibition, distinction between self and others, prediction under uncertainty, and perception of intentions, all of which are important for predicting others’ intention and behavior. We review the literature supporting this claim, ranging in fields from developmental psychology to human neuroimaging and macaque electrophysiology. Because perceiving intentions in others’ actions initiates mentalizing and forms the basis of virtually all types of social interaction, the fundamental issue in social neuroscience is to determine the aspects of physical entities that make an observer perceive that they are intentional beings and to clarify the neurobiological underpinnings of the perception of intentionality in others’ actions.